Applications of Inhalational Nitrous Oxide in Patients as an Alternative to Traditional Narcotics and Sedation Agents in the Emergency Department - Pasadyn, Vanessa (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.